The impact of COVID-19 and rapid policy exemptions expanding on access to medication for opioid use disorder (MOUD): A nationwide Veterans Health Administration cohort study. (1st December 2022) - Livingston, Nicholas A.; Davenport, Michael; Head, Michael; Henke, Rachel; LeBeau, Lavonia Smith; Gibson, Teresa B.; Banducci, Anne N.; Sarpong, Alexis; Jayanthi, Saketh; Roth, Clara; Camacho-Cook, Jessica; Meng, Frank; et al.
Abstract: Background: In March 2020, Veterans Health Administration (VHA) enacted policies to expand treatment for Veterans with opioid use disorder (OUD) during COVID-19. In this study, we evaluate whether COVID-19 and subsequent OUD treatment policies impacted receipt of therapy/counseling and medication for OUD (MOUD). Methods: Using VHA's nationwide electronic health record data, we compared outcomes between a comparison cohort derived using data from prior to COVID-19 (October 2017-December 2019) and a pandemic-exposed cohort (January 2019-March 2021). Primary outcomes included receipt of therapy/counseling or any MOUD (any/none); secondary outcomes included the number of therapy/counseling sessions attended, and the average percentage of days covered (PDC) by, and months prescribed, each MOUD in a year. Results: Veterans were less likely to receive therapy/counseling over time, especially post-pandemic onset, and despite substantial increases in teletherapy. The likelihood of receiving buprenorphine, methadone, and naltrexone was reduced post-pandemic onset. PDC on MOUD generally decreased over time, especially methadone PDC post-pandemic onset, whereas buprenorphine PDC was less impacted during COVID-19. The number of months prescribed methadone and buprenorphine represented relative improvements compared to prior years. We observed important disparities across Veteran demographics. Conclusion: Receipt of treatment was negatively impacted during the pandemic. However, there was some evidence that coverage on methadone and buprenorphine may have improved among some veterans who received them. These medication effects are consistent with expected COVID-19 treatment disruptions, while improvements regarding access to therapy/counseling via telehealth, as well as coverage on MOUD during the pandemic, are consistent with the aims of MOUD policy exemptions. Highlights: The likelihood of receiving MOUD decreased during COVID-19. Despite telehealth increases, therapy/counseling receipt decreased during COVID-19. Among Veterans on MOUD, coverage on buprenorphine increased during COVID-19. Among those on MOUD, months prescribed buprenorphine or methadone increased.